THE INTERNATIONALIZATION AS A COMPONENT OF THE NATIONAL STRATEGY FOR IMPROVEMENT OF HIGHER EDUCATION SPACE IN UKRAINE - Юлія Заячук (National Academy of Educational Sciences of Ukraine, 2021)
The paper is devoted to the study of the issue of internationalization as a component of the national strategy for improvement of the higher education space in Ukraine. It is shown that internationalization of higher education is an instrument of achieving academic goals, values of cooperation and mutual benefit. The internationalization of higher education is seen as a multilevel phenomenon that includes supranational, continental, national, institutional, and individual levels. The national level of internationalization of higher education is analysed in detail on the example of higher education space in Ukraine. It is noted that Ukraine has made significant achievements in the internationalization of higher education through the implementation of the Bologna reform and reform in higher education management and governance. New opportunities for higher education in Ukraine through current international research and educational projects and cooperation with international organizations are highlighted. The institutional level of internationalization of higher education is presented on the example of Ivan Franko National University of Lviv. Some findings of the author research of the attitude of students of Ivan Franko National University of Lviv to the issues of internationalization are also presented.